Wild girl - Reilly Giff Patricia 1935-2021; Patricia Reilly Giff (New York : Scholastic, 2011)
When twelve-year-old Lidie leaves Brazil to join her father and brother on a horse ranch in New York, she has a hard time adjusting to her changed circumstances, as does a new horse that has come to the ranch.
M
640